Ferroelectric‐Nanocrack Switches for Memory and Complementary Logic with Zero Off‐current and Low Operating Voltage. (3rd May 2021) - Guo, Zhe; Guan, Yaodong; Luo, Qiang; Hong, Jeongmin; You, Long
Abstract: Ferroelectric devices have attracted intensive research in memory and logic applications due to their non‐volatility, scalability, and energy efficiency. As an emerging technology, the ferroelectric nanocrack device offers a simple and efficient way to manipulate the device resistance states with a high on/off ratio. Meanwhile, its complementary switching enables the construction of logic gates with a similar way as the complementary metal oxide semiconductor (CMOS) technology. Here, it is demonstrated that the memory and logic functions can be realized by the same device structure with superior electrical performance, such as reliable metallic on‐state contacts, zero off‐state leakage current, and wide working temperature range (–110 to 150 °C). Moreover, the scaling performance has been investigated and the operating voltage can be reduced to average 2.5 V with device scaling down to sub‐micrometers. Following the scaling rule, the operating voltage can shrink largely to sub‐1 V at 100 nm nodes. In addition, the logic gates including NOT, 2:1 MUX, AND, and OR functions have been experimentally demonstrated. It is believed that this work can expand the scope of ferroelectronics and be applicable to logic‐in‐memory computing in the future. Abstract : Ferroelectric‐nanocrack devices can condense memory and logic functions into a single device level with excellent electrical performance such as zero leakage current, 10 9 on/off ratio and sub‐1 V operating voltage. Logic gates including NOT, 2:1 MUX, AND, and OR functions are demonstrated experimentally. Such devices offer a new energy‐efficient hardware platform for logic‐in‐memory applications.